Isolation and molecular characterization of Clostridium perfringens from healthy Merino lambs in Patagonia region, Argentina - Mignaqui, Ana Clara (2016)
The presence and molecular characterization of Clostridium perfringens in healthy Merino lambs over a six-month period was investigated in this study. Overall, a high prevalence of C. perfringens was detected, even in day-old lambs. Even though the majority of the isolates were characterized as being of type A, types C and D were also isolated. Furthermore, a high genetic diversity was observed by PFGE among the type A isolates.